Characterization of active and pH-sensitive poly(lactic acid) (PLA)/nanofibrillated cellulose (NFC) films containing essential oils and anthocyanin for food packaging application - Zabidi, Nurul 'Afifah; Nazri, Farhana; Mohamed Amin Tawakkal, Intan Syafinaz; Mohd Basri, Mohd Salahuddin; Kadir Basha, Roseliza; Othman, Siti Hajar (Elsevier, 2022)
Active and pH-sensitive films of poly(lactic acid) (PLA)/nanofibrillated cellulose (NFC) have been fabricated and tested. The PLA and PLA/NFC films with 1.5% NFC were prepared via solvent casting method, with different loadings of essential oil (EO), including thymol and curry, being added at 5, 10, and 15%. The fixed content of anthocyanin powder (1%) was incorporated into the films as a pH indicator. The active PLA and PLA/NFC films were characterised on their physical, mechanical, thermal, and biodegradation properties. The addition of NFC reduced the tensile strength but increased the flexibility of films due to the plasticizing effect of EOs. The PLA/EO and PLA/NFC/EO films containing curry demonstrated a slightly higher strength than the films with thymol. The flexibility of films was increased at higher loading of EO regardless of the types of EO. The thermal profile demonstrated that the neat PLA film had a higher maximum degradation temperature than the active PLA/EO and PLA/NFC/EO films. The active PLA/EO and PLA/NFC/EO films containing anthocyanin successfully changed its colour in pH 2.0 and 14.0. The PLA/NFC films with thymol and anthocyanin formulation could inhibit fungus growth better in the cherry tomato sample than the PLA/NFC films with curry and anthocyanin.